Optimal range of lymph node dissection in patients with unilateral papillary thyroid carcinoma with lateral cervical lymph node metastasis - Zhang, Liang; Ding, Zhaoming; Han, Jihua; Bi, Wen; Nie, Chunlei (Frontiers in Oncology, 2023)
Background: Whether patients with unilateral papillary thyroid carcinoma (PTC) with lateral cervical lymph node metastasis (LLNM) require prophylactic central regional lymph node dissection (CLND) remains unclear. Herein, we investigated the independent risk factors associated with contralateral central lymph node metastasis (cCLNM) in unilateral PTC with LLNM and analyzed the optimal extent of lymph node dissection by comparing the 5-year recurrence-free survival rates.We retrospectively analyzed 695 patients with unilateral papillary thyroid carcinoma and lateral cervical lymph node metastasis. Factors including sex, age, multifocal, location of primary tumor, tumor diameter, capsule invasion, thyroid nodular goiter, Hashimoto thyroiditis, ipsilateral central lymph node metastasis(iCLNM), and lateral cervical lymph node metastasis were analyzed using univariate and multivariate logistic regression analyses to explore the independent risk factors of cCLNM. Propensity scores were matched to compare the 5-year recurrence-free survival rates in patients divided by different lymph node metastases and dissections.Results: Of all patients who underwent bilateral (b)CLND, 52% (149/286) had cCLNM. Receiver operating characteristic (ROC) curve analysis was performed on 286 patients who underwent bCLND, for which a tumor diameter of 20.5 mm and number of LLNM of 3.5 were used as the thresholds for predicting cCLNM. The 5-year recurrence-free survival (RFS) rates in the cCLNnegative and cCLN-positive groups were 98.6% and 91.2%, with statistically significant differences (P=0.034). The 5-year RFS rates showed no significant difference between the ipsilateral (i)CLND and bCLND groups (P=0.235). Multifactorial regression analysis showed that tumor diameter >2 cm, presence of iCLNM, and number of LLNM >3 were independent risk factors of cCLNM.But male sex, young age (<45 years), multifocality, location of primary tumor, capsule invasion, thyroid nodular goiter, and Hashimoto thyroiditis were not associated with cCLNM.Not all unilateral PTC with LLNM require prophylactic cCLND; however, prophylactic cCLND is necessary in cases which display high-risk factors for cCLNM, including primary diameter >2 cm, iCLNM, and number of LLNM >3.